Severely ill and high-risk COVID-19 patients exhibit increased peripheral circulation of CD62L+ and perforin+ T cells - Lesteberg, Kelsey E.; Araya, Paula; Waugh, Katherine A.; Chauhan, Lakshmi; Espinosa, Joaquin M.; Beckham, J. David (Frontiers in Immunology, 2023)
The emergence of SARS-CoV-2, which causes COVID-19, has led to over 400 million reported cases worldwide. COVID-19 disease ranges from asymptomatic infection to severe disease and may be impacted by individual immune differences. We used multiparameter flow cytometry to compare CD4+ and CD8+ T cell responses in severe (ICU admitted) and non-severe (admitted to observational unit) hospitalized COVID-19 patients. We found that patients with severe COVID-19 had greater frequencies of CD4+ T cells expressing CD62L compared to non-severe patients and greater frequencies of perforin+ CD8+ T cells compared to recovered patients. Furthermore, greater frequencies of CD62L+ CD4+ and CD8+ T cells were seen in severely ill diabetic patients compared to non-severe and non-diabetic patients, and increased CD62L+ CD4+ T cells were also seen in severely ill patients with hypertension. This is the first report to show that CD62L+ T cells and perforin+ T cells are associated with severely ill COVID-19 patients and are significantly increased in patients with high-risk pre-existing conditions including older age and diabetes. These data provide a potential biological marker for severe COVID-19.